2021
DOI: 10.3233/jad-210181
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Interactions Between APOE and Klotho Genotypes on Cognitive, Dementia, and Brain Imaging Metrics in UK Biobank

Abstract: Recent research suggests genetic variation in the Klotho locus may modify the association between APOE ɛ4 and cognitive impairment. We tested for associations and interactions between these genotypes versus risk of dementia, cognitive abilities, and brain structure in older UK Biobank participants. Klotho status was indexed with rs9536314 heterozygosity (versus not), in unrelated people with versus without APOE ɛ4 genotype, corrected for various confounders. APOE ɛ4 associated with increased risk of dementia, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Non-white and Latino individuals were excluded from the analysis since they represented less than 5% of the initially identified participants. This was done to increase homogeneity in the analyzed cohort and reduce the potential confounding effect of population stratification, which is consistent with similar studies [ 26 , 27 ]. After processing genetic data as described below, 665 participants from the combined ADNI and NACC cohorts were selected for final analysis.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…Non-white and Latino individuals were excluded from the analysis since they represented less than 5% of the initially identified participants. This was done to increase homogeneity in the analyzed cohort and reduce the potential confounding effect of population stratification, which is consistent with similar studies [ 26 , 27 ]. After processing genetic data as described below, 665 participants from the combined ADNI and NACC cohorts were selected for final analysis.…”
Section: Methodsmentioning
confidence: 54%
“…One potential mechanism concern opposing effects of KL -VS het+ and the ε4 allele on cognitive reserve. Several studies have shown that older, cognitively normal individuals with KL -VS het+ perform better on a number of cognitive tasks compared to individuals with KL -VS het− [ 4 , 20 , 27 ], while the opposite effect is true of the ε4 allele, where carriers perform worse than non-carriers [ 33 , 34 ]. The cognitive benefits linked to elevated klotho levels in KL -VS het+ subjects have been examined using transgenic rodent models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the selected imaging phenotypes were a priori associated with worse cognitive ability and decline, namely for dMRI those were global and tract-specific fractional anisotropies (e.g. ( Tank et al, 2021 )) (See Supplementary Table 1 for details). The diffusion tensor was used to calculate the diffusion eigenvectors and eigenvalues (λ1, λ2, λ3), which represent the main direction of diffusion and related diffusivity.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have only observed γ-KL in brown adipose tissue and eyeballs and have not yet found an association with the FGFs/FGFRs system (Zhang et al, 2017;Ma et al, 2021). Although much evidence suggests that α-KL has essential effects on cognition and memory, these studies have focused on s-KL rather than m-KL as a ligand for FGF-23 (Cararo-Lopes et al, 2017;Li et al, 2017;Zhao et al, 2020;Tank et al, 2021). These two α-KL have different structural features and physiological roles.…”
Section: Co-receptor Kl Proteinmentioning
confidence: 99%